A survey of economic indices of plastic wastes recycling industry - Malek Hassanpour (Iranian Journal of Health, Safety and Environment, 2015)
Numerous small recycling units of plastic wastes have been currently constructed heedless to study of economic indices in Iran. Pay attention to the prominent performance of the industrial sector for economic development and its priority for fortifying other sectors to implement job opportunities, survey of the economic indices beckon the stakeholders and industries owners. The main objective of this study was a survey of economic indices in small recycling unit of plastic wastes. Therefore, the practice of computing the economic indices was performed using empirical equations, professional experiences and observations in site of the industry in terms of sustainability performance. Current study had shown the indices values such as value-added percent, profit, annual income, breakeven point, value-added, output value, data value, variable cost of good unit and production costs were found 62%, $ 366558, $ 364292.6, $ 100.34, $ 423451.25, $ 255335.75, $ 678787, $ 389.65 and $ 314494.4 respectively. The breakeven point about 15.93%, the time of return on investment about 1.12 (13.7 months) were represented that this industry slightly needs long time to afford the employed capital and starts making a profit.